Metaphorical conceptualisations in the religious tweets of a Nigerian politician - Nnamele, Adamma Maryann; Mohd Kasim, Zalina (Human Resource Management Academic Research Society (HRMARS), 2023)
Communicating with the masses is the life-blood of politicians and it is vital that politicians are adept at using language to win the masses over to themselves. This study seeks to examine conceptual metaphors in the tweets of a Nigerian politician in order to unravel the discourse value of the linguistic metaphors contained in the selected tweets. The politician, Senator Dino Melaye, uses several metaphors in his tweets, which happen to be religious in nature. The objectives of the study are to identify the linguistic metaphors contained in the religious tweets and examine the underlying conceptual metaphors in the politician’s tweets. Using Lakoff and Johnson’s Conceptual Metaphor Theory (CMT) and Metaphor Identification Procedure by Pragglejaz Group, the metaphoricity of his prayer points is analyzed to determine the underlying conceptual metaphors. The findings show that some domains have more linguistic expressions than others. WAR is the most frequently used source domain as it has the highest number of metaphorical expressions. Based on the analysed data, this study reveals that he employs these metaphors to evoke certain notions in his followers. The study further strengthens the literature that metaphor is a powerful tool for persuasion.